Edna St. Vincent Millay collection - Millay, Edna St. Vincent, 1892-1950.; Millay, Kathleen, -1943.; Oliver, Mary, 1935-
Correspondence, poetry, plays, family papers, photographs, and other papers relating chiefly to Millay's life and literary career. Includes short stories by her sister Kathleen Millay and an excerpt from Blue Pastures by Mary Oliver. Subjects include poetry, operas, producing The King's Henchmen, Millay's biography, her relationship with George Dillon, the death of Elinor Wylie, disposition of Millay's papers, and social activities. Correspondents include Eugen Boissevain, Lola Bronstein, Witter Bynner, George Dillon, Charles Hamilton, Alice Baur Hodges, Anne Lanfranchi, Nino Lanfranchi, Nancy Milford, Norma Millay, Frank Shay, Nan Sussmann, and Deems Taylor.
Author and poet.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Boissevain, Eugen, -- -1949 -- Correspondence; Bronstein, Lola -- Correspondence; Bynner, Witter, -- 1881-1968 -- Correspondence; Dillon, George, -- 1906-1968.; Dillon, George, -- 1906-1968 -- Correspondence; Hamilton, Charles, -- 1875-1961 -- Correspondence; Hodges, Alice Baur -- Correspondence; Lanfranchi, Anne -- Correspondence; Lanfranchi, Nino -- Correspondence; Milford, Nancy -- Correspondence; Millay, Norma -- Correspondence; Shay, Frank, -- 1888-1954 -- Correspondence; Sussmann, Nan, -- 1888-1954 -- Correspondence; Taylor, Deems, -- 1885-1966 -- Correspondence; Wylie, Elinor, -- 1885-1928.; The king's henchman: a play in three acts; American literature; American poetry; Operas; Authors; Poets